2001
DOI: 10.1046/j.1439-0418.2001.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Day‐degree models for predicting the generation time and flight activity of local populations of Lobesia botrana (Den. & Schiff.) (Lep., Tortricidae) in Greece

Abstract: The generation time of Lobesia botrana (Den. & Schiff.) was estimated as the number of day‐degrees required between the start of a flight and the start of the following flight in two regions in northern Greece. The day‐degrees required for the first generation (x=339.3, Naoussa; x=275.6, Thessaloniki) were significantly shorter than for the second (x=751.5, Naoussa; x=833.8, Thessaloniki) and the third generations (x=899.5, Naoussa; x=1197.0, Thessaloniki). Nonlinear models were developed using trap catches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 13 publications
1
39
0
3
Order By: Relevance
“…Variability between generations for OM has been observed also in Turkey (Kumral et al ., 2005) as well as for other species such as Platynota idaeusalis (Walker), Argyrotaenia velutinana (Walker) and Lobesia botrana (Rock et al , 1993; Milonas et al , 2001). The results suggest that for OM, timing for these flight activities is related to host tree phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Variability between generations for OM has been observed also in Turkey (Kumral et al ., 2005) as well as for other species such as Platynota idaeusalis (Walker), Argyrotaenia velutinana (Walker) and Lobesia botrana (Rock et al , 1993; Milonas et al , 2001). The results suggest that for OM, timing for these flight activities is related to host tree phenology.…”
Section: Discussionmentioning
confidence: 99%
“…1984). For the grapevine moth several models have been proposed (Touzeau 1981; Cravedi and Mazzoni 1994; Milonas et al. 2001), including one which takes in account the relative influence of specific climatic factors on the dynamics of these insects (Schmidt et al.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, two distinct generations of L. botrana occur in Switzerland (Moraviea et al, 2006), although three or even four may occur in southern Europe (Bovey, 1966;Gabel & Mocko, 1984;Milonas et al, 2001;Roditakis & Karandinos, 2001). Martin-Vertedor et al (2010) found four and a half generations in western Spain with a partial fifth recorded during 2006.…”
Section: Regional Dynamics Of Grape and L Botranamentioning
confidence: 99%
“…The proper timing of conventional insecticides targeting adult flights is critical for effective control (Caffarelli & Vita, 1988;Oliva et al, 1999;Boselli & Scannavini, 2001) and several phenological models have been developed to forecast the flight of the different generations of adult moths (Gabel & Mocko, 1984;Caffarelli & Vita, 1988;Del Tío et al, 2001;Milonas et al, 2001;Moraviea et al, 2006;Gallardo et al, 2009;Gutierrez et al, 2012;Gilioli et al, 2016).…”
Section: Control Of L Botranamentioning
confidence: 99%